Penciptaan Hiasan Dinding melalui Teknik Batik Kombinasi Trapunto - Haryati Dwi Suhestin; Tiwi Bina Affanti (Texture:Art and Culture Journal, 2022)
The creation of wall hangings is motivated to meet the needs of aesthetic elements in spaces that have the function of helping to build the atmosphere in a room. The reason for visual selection by processing the natural nuance is because the scenery in the natural nuance has the ability to give the impression of comfort and serenity to its inhabitants. The results of the creation of this Final Project are as follows: Creation of visual design by processing the theme of the natural atmosphere through batik  techniques and trapunto techniques for wall decoration totaling eight (8) visual designs. The overall visual design processes the elements contained in the natural atmosphere along with the stories in them which are illustrated through a decorative styling, using a two-size 110x80cm and 80x0cm philip berkolin cotton fabric that is done with Remasol staining.